Exploring Bohdan Lepky’s Translation Ethics Using Linguistic Inquiry and Word Count - Zasiekin, Serhii (Lesya Ukrainka Volyn National University, 2021)
The present empirical study aims to outline ethical landmarks of Bohdan Lepky, the renowned Ukrainian writer and translator, in his Ukrainian translation of Salomé by Oscar Wilde. We assess the ethics of translation data defined by Kalina (2015) in terms of accuracy, impartiality, and confidentiality. In order to address these ethical issues, the study envisaged the following steps. First, source and target texts were analyzed using the Linguistic Inquiry and Word Count (LIWC) computerized program based on its built-in French 2007 and Ukrainian 2015 dictionaries. Second, all 'style words' (Tausczik & Pennebaker, 2010) represented by functional words, e.g., conjunctions, prepositions, and pronouns that bear procedural meaning, were compared in both texts. Findings showed that the translator followed the ethical "tradition of sameness" (Wyke, 2011), being less "visible" (Venuti, 1995) in his target language version. Despite a greater number of impersonal pronouns causing slight implicitation, we observed no traces of simplification or explicitation deforming tendencies in Lepky's translated text. Similar indices of conjunctions and prepositions, and the average number of words per sentence in both texts, confirmed the accuracy of meaning and style. Although markers of oral speech (fillers) prevailed in translation, this strategy manifests his agency and attempt to be ethically "accountable" for his product in the sense of Schlesinger’s (1989) "equalizing." This shift moves along the oral-literate continuum towards more natural, i.e., rich in pragmatic discourse markers (Schiffrin, 1989) oral communication. The LIWC psychological category of "affect" filled with emotionally charged words was less dense in the Ukrainian version, contributing both to the translator's "ethics of difference" (Venuti, 1999) and his impartiality. Thus, results of the LIWC-processed data demonstrated high ethical standards of translating Bohdan Lepky met in his Ukrainian rendition of Salomé by Oscar Wilde.
Keywords: Salomé; Oscar Wilde; Bohdan Lepky; ethics of translation; translation universals; LIWC